2018
DOI: 10.1007/s00894-018-3660-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical sensors based on N-substituted polyaniline derivatives: reactivity and adsorption studies via electronic structure calculations

Abstract: Conjugated organic polymers represent an important class of materials for varied technological applications including in active layers of chemical sensors. In this context, polyaniline (PANI) derivatives are promising candidates, mainly due to their high chemical stability, good processability, versatility of synthesis, polymerization, and doping, as well as relative low cost. In this study, electronic structure calculations were carried out for varied N-substituted PANI derivatives in order to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
(77 reference statements)
0
13
0
Order By: Relevance
“…Such indexes describe how the electronic populations of the atoms change after the releasing/withdrawing of electrons in/from a given system, allowing to identify molecular sites that are prone to interact with nucleophiles (f + ) or electrophiles (f − ) [31]. In particular, these descriptors have been successfully employed in the study of polymers [[32], [33], [34], [35]] and molecules reactivity [11,27,31,36,37]. The simulations were carried out in vacuo and without temperature effects using the same DFT/B3LYP/6-31G approach employed in the optimizations.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such indexes describe how the electronic populations of the atoms change after the releasing/withdrawing of electrons in/from a given system, allowing to identify molecular sites that are prone to interact with nucleophiles (f + ) or electrophiles (f − ) [31]. In particular, these descriptors have been successfully employed in the study of polymers [[32], [33], [34], [35]] and molecules reactivity [11,27,31,36,37]. The simulations were carried out in vacuo and without temperature effects using the same DFT/B3LYP/6-31G approach employed in the optimizations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The simulations were carried out in vacuo and without temperature effects using the same DFT/B3LYP/6-31G approach employed in the optimizations. Hirshfeld partition charge model was employed to estimate the electronic populations to avoid negative CAFIs [ [31], [32], [33], [34], [35]].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Besides presenting unique properties that allow their use in varied technological applications, polymeric materials also present reasonable chemical stability, ease of synthesis and low relative costs. In addition, a number of functionalizations can be made, allowing a wide range of optoelectronic responses for a variety of applications, 11 including as active layers of chemical sensors 12–14 …”
Section: Introductionmentioning
confidence: 99%
“…Previous works conducted by our group have shown the relevance of preliminary studies of the local reactivities to identify promising materials/sites for adsorption analysis 12–14 . In particular, density functional theory (DFT) based calculations and fully atomistic reactive molecular dynamics (FARMD) simulations have shown that the evaluation of the local reactivities and electrostatic potentials allows the identification of effective adsorption centers on the polymer structures 13 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Pani can be used as an electrode material 8,9 , corrosion protection of metals 10,11 , in the manufacture of secondary batteries 12 , in microelectronics 13 and as an electrochromic material [14][15][16] . Future high-tech applications in the domain of chemical sensors have also been proposed [17][18][19] . Pani can be prepared by various techniques, namely electrodeposition 20,21 , template synthesis 22,23 , seeding 24 , and interfacial polymerization 25 .…”
Section: Introductionmentioning
confidence: 99%